Gas geochemistry of the hot springs gas in Fujian province, SE China: insight into the deep faults and seismic activity - Liao, Lixia; Zhou, Yueyong; Lin, Zhiying; Wang, Xiaowei; Chen, Wei; Li, Jiyu; Zheng, Chenhe; Yu, Wenjun; Li, Xingmei; Liu, Jianda (Frontiers in Earth Science, 2023)
Hot spring gases are less vulnerable to atmospheric contamination, making them capable of carrying more direct information about deep geological environments and seismic activity. In this paper, to explore the geochemical signals of hot spring gases to tectonic activity and earthquakes in Fujian and Taiwan, we collect geothermal gas samples from 29 locations from January 2021 to December 2022 for determining their gas composition, He-Ne-C isotopes, radon contents, and gas flow rates. Our studies suggest that there is a strong mantle source degassing process in the Fujian region, with a high degree of crust mantle connectivity. Deep thermal fluids play a significant controlling role in regional seismic activity. Areas with relatively strong upwelling of deep fluids are the main regions of regional seismic activity, and seismic intensity is positively correlated with mantle-derived heat flow. The high values of hot spring gas isotopes and gas flow velocity in the time domain hold paramount significance in facilitating short-term and imminent analyses of ML 6.0 and above earthquakes in Taiwan. This will have great potential application for short-term precursors of earthquakes globally. We thus believe that this topic will be of broad interest to the readership of the Front. Earth Sci.